PENGARUH LATIHAN KEKUATAN OTOT LENGAN MELALUI PULL UP TERHADAP PENINGKATAN SPEED TRACK ATLET FEDERASI PANJAT TEBING INDONESIA BANJARBARU - Mita Erliana (Lambung Mangkurat University, 2015)
Effect of Arms’ Muscle Strength Exercise Through Pull Up on Improving of performance of Speed Track for the Athletes of Indonesian Rock Climbing Federation, Banjarbaru. This research uses the quasi experimental method. The population in this research are all the athletes of Indonesian Rock Climbing Federation, Banjarbaru. Population using the total sampling technique.Data collected in the form of quantitative data are the data of testing result on speed tract.The result of analysis on the differences of the results of the pretest and the posttest shows that performance of speed tract indicates t-count= 4.440 with p = 0.004; p is lower than 0.05 (p <0.05), thus t-count is significant. The result of research shows that: there is an effect of pull up exercise on the performance of speed tract for the athletes of Indonesian Climbing Federation, Banjarbaru. Keywords: Effect, pull up, and performance of Speed Track.